Molecular basis for dominantly inherited inclusion body beta-thalassemia. - Thein, S L (1990)
Analysis of the molecular basis of dominantly inherited beta-thalassemia in four families has revealed different mutations involving exon 3 of the beta-globin gene. It is suggested that the phenotypic difference between this condition and the more common recessive forms of beta-thalassemia lies mainly in the length and stability of the abnormal translation products that are synthesized and, in particular, whether they are capable of binding heme and producing aggregations that are relatively resistant to proteolytic degradation.